Hypersensitivity Pneumonitis Associated with Red-Vented Bulbul: A New Encounter of Bird Related Hypersensitivity Pneumonitis. (9th December 2019) - Amarasinghe, W. D. N. L.; Jayasekara, R.; Jayamanne, B. D. W.; Nalaka, T. D. K.; Amarasiri, W. A. D. L.; Punchihewa, R.; Fernando, A.
Abstract : Bird related hypersensitivity pneumonitis (HP) is becoming more common than other forms of HP around the world. We present two cases of HP, associated with exposure to visiting birds which had nested within their homes in semi urban areas of Colombo, Sri Lanka. A 65-year-old female (case 1) and a 61-year-old male (case 2) presented to the chest clinic complaining of gradually progressive and persistent chronic dry cough and dyspnoea during the year 2018. Both were found to have close contact with red-vented bulbuls (Konda kurulla) in their homes for more than 6 months prior to onset of symptoms and denied any other risk exposures in detail history taking. In both patients, high-resolution computed tomography chest (HRCT) showed centrilobular nodules of ground glass density with significant lobular air trapping. Video-assisted thoracoscopic (VATs) lung biopsy of case 1 showed patchy and focal interstitial thickening with lymphocytic infiltrate, minimal fibrosis, and few noncaseating granulomata within the interstitium. Transbronchial lung biopsy of case 2 showed thickened alveolar septae with lympho-histiocytic infiltrate and occasional neutrophils and eosinopils. Both showed severe reduction in forced vital capacity (FVC) at presentation. Multidisciplinary diagnosis of HP associated with red-vented bulbuls was made. Both achieved good improvement in clinical, lung function, and radiological assessment following removal of offending antigen exposure and treatment with oral corticosteroids.